Toponymy Analysis of Village Naming in Ternate - Nur Fajrhi; Fitriningsih Pratiwi Mahmud; Sartika Putri Sailuddin; Ahmad Rifani Talaohu; Sulmi Magfirah (Jurnal Sinestesia, 2023)
Ternate is one of the cities in North Maluku, located right beneath Gamalama Mountain. Ternate was once a trade center in the 13th century and became a melting pot for people from different countries with different purposes. There were Portuguese, Dutch, and Spanish with the aim of colonizing, and there were Arabian, Chinese, and locals outside Ternate, such as people from Halmahera, Sulawesi, Maluku, Sumatra, and Java, who came for trading. The arrival of these people contributes not only to language adaptation but also to place names known as toponymy. There are several relevant studies concerning toponymy in Indonesia, but they have yet to be done in Ternate. Hence, this research aims to: 1) analyze the morphological process of the villages naming in Ternate and 2) provide toponyms classification of the villages naming in Ternate. The primary data are taken from Ternate Dalam Angka, a statistical data from BPS Ternate, which contains 59 villages/sub-districts named in Ternate. The data was then analyzed and triangulated through in-depth interviews and literature studies. The data are presented both formally and informally. The analysis results show morphological processes concerning zero derivation, reduplication, compounding, abbreviation, back-formation, combination, borrowing, and phrases that occurred in the villages named in Ternate. The findings also attest to a theory proposed by George R. Stewart (2012) regarding toponymy classification of village naming in Ternate, in which there are descriptive, incident, possessive, commemorative, euphemistic, folk etymologies, manufactured, shift, mistake, descriptive + manufactured, euphemistic + manufactured, euphemistic + manufactured, and unknown.